PERSEPSI ORANG MUDA KATOLIK PAROKI MATER DEI TENTANG MERAYAKAN HARI MINGGU SEBAGAI HARI TUHAN - Don Bosco Karnan Ardijanto; Meiry Chrimiyati (Lembaga Penelitian STKIP Widya Yuwana, 2018)
Sunday was a very special day to get together with our brothers and sisters in the Church, to give thanks to God and the memory of the passion, resurrection andglory of the Lord Jesus. In addition, Sunday is recommended as a day to develop the piety of the faithfull, as a day of excitement and a day free from work. There is a reason that is not the right of the people to go to church on Sunday or not. First, they come out of habit. Second, there are people who think that they can pray better if done at home alone, so no need to go to church on Sundays. Of these concerns, researched